PERBANDINGAN EFEKTIVITAS BIAYA TERAPI KOMBINASI OBAT METFORMIN-GLIMEPIRIDE DAN ACARBOSE-GLIMEPIRIDE DI RSUD SUMEDANG TAHUN 2021 - Nden Ajeng Tresnawati (2022)
Type 2 Diabetes Mellitus (DM) is one of the cardiometabolic diseases with the highest prevalence worldwide, including Indonesia. The increasing number of type 2 diabetes mellitus is known to have become an economic burden on health sector in Indonesia. There are several options in the treatment of Type 2 DM either with monotherapy or combination of several drugs. At present, metformin, sulfonylurea, and acarbose have become common drugs in the treatment of Type 2 DM in Indonesia. Variations in antidiabetic drug therapy will cause differences in cost and effectiveness of therapy. The purpose of this study is to analyze the cost-effectiveness of the combination therapy of metformin-glimepiride and acarbose-glimepiride antidiabetic drugs in patients with Type 2 DM in the Outpatient Installation at RSUD Sumedang in 2021 based on the hospital's perspective. This study uses a cross-sectional design, data collection was carried out by documenting or recording medical record data and patient costs during the period of January-December 2021. A comparison of the effectiveness of therapy (∆GDS) and direct medical costs is carried out in the two groups. The results of the analysis showed that there was no significant difference in GDS in the combination of metformin-glimepiride and acarbose-glimepiride (mean difference 10.70 mg/dL-1; p-value = 0.457). The average total direct medical costs of the acarbose-glimepiride group was higher than that of the metformin-glimepiride group and there was a significant difference between the average costs of the antidiabetic drugs (p-value = 0.000). Based on the calculation of the cost-effectiveness results, the combination of metformin-glimepiride therapy is more cost effective than acarbose-glimepiride with an ACER value of metformin-glimepiride Rp.3.037,48. Keywords: Acarbose, cost effectiveness analysis, glimepiride, metfotmin, type 2 diabetes mellitus